Effect of hydrocolloids on the quality of restructured hams with duck skin. (5th October 2018) - Kim, Tae-Kyung; Shim, Jae-Yun; Hwang, Ko-Eun; Kim, Young-Boong; Sung, Jung-Min; Paik, Hyun-Dong; Choi, Yun-Sang
ABSTRACT: We investigated the quality of duck ham restructured with various hydrocolloids (Alginic acid, Konjac, Carrageenan) on proximate composition, cooking loss, emulsion stability, pH, color, texture profile analysis (TPA), protein solubility, sensory characteristics, and apparent viscosity. Restructured duck ham was prepared as follows: control with no hydrocolloids, T1 (Alginate 1%), T2 (Alginate 0.5% + Konjac 0.5%), T3 (Alginate 0.7% + Konjac 0.3%), T4 (Alginate 0.5% + Carrageenan 0.5%), and T5 (Alginate 0.7% + Carrageenan 0.3%). The restructured duck hams with hydrocolloids had higher value for moisture content, ash content, and apparent viscosity than the control ( P < 0.05). The cooking loss, total expressible fluid and fat separation, redness, hardness, cohesiveness, gumminess, and chewiness of restructured duck hams with hydrocolloids was lower than those of the control ( P < 0.05). The sensory score for overall acceptability of restructured duck ham with T1 (1% alginate) and T2 (0.5% alginate + 0.5% konjac) was higher than that of the control ( P < 0.05). Thus, this study showed that adding 1% alginate or 0.5% alginate + 0.5% konjac in restructured duck ham formulations results in optimized quality characteristics.